Two large rodents from the Middle Miocene of Chiang Muan, northern Thailand - Nishioka Y. (2017)
© 2016, © 2015 Taylor & Francis. Two large rodents from the Middle Miocene (13.0–12.4 Ma) were discovered at the Chiang Muan Coal Mine, northern Thailand. One, a beaver (Anchitheriomys, Castoridae), has large cheek teeth with a high crown, the crown base wider buccolingually, basically six fossettes/sinuses, enamel foldings strongly complicated, and hypoflexus/flexid shallow dorsoventrally. Based on dental morphology, this form is more similar to Anchitheriomys suevicus from Europe than to Anchitheriomys tungurensis from northern China. The other species is considerably larger than Anchitheriomys, based on incisor measurements, and lacks longitudinal grooves or deep ridges on the enamel surface, which are diagnostic of Anchitheriomys. Furthermore, the inner enamel observed by scanning electron microscope has uniserial Hunter-Schreger bands, similar to castorids rather than hystricids. This species is indeterminate taxonomically, but differs from any rodents known from Asia. The distribution of Anchitheriomys was previously restricted between the latitudes 30°N and 50°N, but this occurrence in northern Thailand at low latitude (ca. 19°N) suggests that it had wider distribution on the Eurasian continent.